Interneuron Types and Their Circuits in the Basolateral Amygdala - Hájos, Norbert (Frontiers in Neural Circuits, 2021)
Basolateral amygdala is a cortical structure based on its cell types, connectivity features and developmental characteristics. This part of the amygdala is considered to be the main entry site of processed and multisensory information delivered via cortical and thalamic afferents. Although GABAergic inhibitory cells in the basolateral amygdala comprise only 20% of the entire neuronal population, they provide an essential control over proper network operation. Previous studies have uncovered that GABAergic cells in the basolateral amygdala are as diverse as those present in other cortical regions, including the hippocampus and neocortex. To understand the role of inhibitory cells in various amygdala functions, we need to reveal the connectivity and input-output features of the different types of GABAergic cells. Here, I review the recent achievements in uncovering the diversity of GABAergic cells in the basolateral amygdala with specific focus on the microcircuit organization of these inhibitory cells.